THE EFFECT OF BRAND IMAGE, PRICE PERCEPTION AND ONLINE CUSTOMER REVIEW ON PURCHASE DECISIONS OF AZARINE COSMETIC PRODUCTS IN DENPASAR CITY - Ni Putu Siska Pratiwi; I G Ng A Gede Eka Teja Kusuma; Made Pradnyan Permana Usadi (Jurnal Bakti Saraswati (JBS), 2026)
In an era of increasingly intense competition within the cosmetic industry, companies are required to comprehensively understand the factors influencing consumer purchase decisions. The emergence of numerous new brands, issues related to brand image, price sensitivity, and the proliferation of consumer reviews on digital platforms have made consumer behavior more dynamic and complex. This research is conducted to analyze the effects of brand image, price perception, and online customer review on purchasing decisions of Azarine Cosmetic products in Denpasar City. This research employs a quantitative approach using a survey method. The data were collected by administering questionnaires to consumers who have previously used Azarine Cosmetic products in Denpasar ity, utilizing a non-probability sampling technique. Data analysis was conducted using multiple linear regression analysis to examine the influence of each independent variable on purchasing decisions as the dependent variable. The analysis demonstrates that brand image has a positive and significant effect on purchasing decisions, suggesting that a strong brand image can enhance consumer trust and purchase intention. Price perception also demonstrates a positive and significant effect on purchasing decisions, indicating that the alignment between price, quality, and product benefits is a key consideration for consumers. Furthermore, online customer review have a positive and significant effect on purchasing decisions, highlighting the important role of consumer reviews in shaping confidence and reducing uncertainty prior to purchase. These findings provide important implications for cosmetic companies to strengthen brand image, set competitive pricing strategies, and strategically manage consumer review